Impact of entrepreneurial orientation on strategic alliances and the role of top management - Antonio Benedito de Oliveira Junior; Felipe Mendes Borini; Roberto Carlos Bernardes; Mauro José de Oliveira (RAE: Revista de Administração de Empresas, 2016)
The management literature draws attention to the gap of strategic alliances (SA) in the paradigm of entrepreneurial orientation (EO). The aim of this paper is to propose a model where EO is associated with SA, this relationship being influenced by its predecessor (top management), and EO working as a multidimensional construct. Data collected from 101 Brazilian firms were analyzed using structural equation modeling and supported those hypotheses. Improving firms’ EO, particularly risk taking (RT), is important in order to promote SA. Obviously, top management can influence SA, but firms with an RT competence are more likely to promote SAs and conduct their implementation. Therefore, the present study offers the following contributions: (1) consolidating the EO construct by using it in a multidimensional way in a reflexive model, particularly the risk dimension; (2) advancing studies relating EO and SA by showing that top management has a significant influence on the EO-SA relationship; (3) the model used is robust and representative of the field of strategy and entrepreneurship as it explained 25.5% of the EO-SA relationship; (4) we suggest that EO should be used to increase SA and firm performance, which can reduce entrance barriers and business risks, particularly for small and medium-sized enterprises (SMEs).